Механізми становлення мовлення дітей у ранньому віці - Брушневська, Ірина (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті автор обґрунтовує необхідність вивчення механізмів формування мовленнєвої діяльності дітей у ранньому віці. Вказує на пріоритетність мовлення у становленні особистості, суперечливість та взаємообумовленість цього процесу. Аналізує різнопланові погляди науковців на етапи та специфіку розвитку мовленнєвої діяльності дітей раннього віку, зосереджуючи увагу на психолінгвістичній мотивації виникнення певних мовленнєвих одиниць. Автор наголошує на необхідності поетапного вивчення появи складових мовлення в онтогенезі. Розглядає процес розвитку мовленнєвої діяльності дітей комунікативного спрямування за основними складовими мовленнєвої діяльності: фонетико-фонематична, лексична, граматична, синтаксична. Аргументує, що виникнення та розвиток всіх цих процесів в онтогенезі зумовлені потребою дітей раннього віку у мовленнєвому спілкуванні, відбуваються в процесі безпосередньої комунікативної взаємодії з дорослими та однолітками, навколишнім середовищем. Аналіз виявлених у ході дослідження механізмів розвитку мовленнєвої діяльності дошкільників засвідчив складність, поетапність, взаємообумовленість і залежність розвитку всіх його складових від комунікативної потреби. The interpretation of the mechanisms of children' speech, the formation of its prerequisites, the improbability of development, the impact of endogenous and exogenous factors on its development are possible from modern positions are possible only in the condition of clear and conscious understanding of the essence of speech activity, its structure, features of formation in ontogenesis. Speech priority in the formation of the personality of child at the early ages is indisputable, because it promotes the formation of its intellectual potential, increases cognitive activity, qualitatively broadens the worldview, stimulates and enriches communicative skills. In the article the author substantiates the necessity of studying the mechanisms of formation of speech activity of children at early ages. Indicates the complexity, inconsistency and interdependence of this process. Analyzes the diverse views of scientists on the stages and specifics of the development of speech activity of young children, focusing on the psycholinguistic motivation of the emergence of certain speech units. The author emphasizes the need for a step-by-step study of the appearance of the speech components in ontogenesis. Child's speech develops in the process of ontogenesis in parallel with physical and mental, it is also an indicator of general psychophysical development. The assimilation of native speech by a child happens with strictly defined regularity and is characterized by a number of features which are common for all children. The process of development of children’s speech activity of the communicative direction of the main components of speech activity has considered phonetic-phonemic, lexical, grammatical, syntactic. Claim that that the emergence and development of all these processes in ontogenesis is conditioned by the necessity of young children in speech communication has argued. It occurs in the process of direct communicative interaction with adults and coevals, the environment. The analysis of the mechanisms of the development of speech activity of preschool children has revealed the complexity, phasing, interdependence and the dependence of the development of all its components from the communicative needs.
Keywords: діти раннього віку; мовлення; онтогенез; механізми